Blogging 101: the effectiveness of a reflective online journal as part of a final year placement unit - Wolf, Katharina (University of Western Sydney, 2008)
Blogs have been around for roughly half the history of the World Wide Web and are increasingly used as part of the communications mix and, however, they are still only scarcely integrated in the teaching toolkit. This study reviews the effectiveness of blogs, or online journals, within the context of a compulsory, final year placement unit, with a particular focus on combating feelings of isolation, enabling a broader insight into the industry and encouraging an international perspective on industry practice. The results suggest that despite the high administrative workload experienced by academics, the introduction of the Reflective Blog was an overall success, suggesting that blogs are particularly useful in the context of an individual tuition unit, effectively shifting the focus away from mainstream, standardised textbooks to 'offbeat', interactive teaching tools, encouraging peer to peer learning.